2013
DOI: 10.1055/s-0032-1333061
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Parameter Analysis on Modified Sauvé-Kapandji Procedure

Abstract: Severe arthritis or derangement of the distal radioulnar joint (DRUJ) leads to instability of the DRUJ, and the subluxation of the ulna causes pain on motion, loss of grip strength, and a restriction of forearm rotation. 1 A variety of surgical procedures have been described to treat these. 2 In 1912, Darrach described a resection of the ulnar head. 3 Although this procedure could successfully restore forearm rotation, serious postoperative complications frequently occurred, such as a further loss of grip stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Simple OBF reconstruction can generally cause wrist longitudinal instability, DRUJ instability and chronic pain [10]. Ota et al [21] also consider that the wrist width loss after Sauvé-Kapandji procedure is associated with the aggravated carpal ulnar deviation, therefore, attention should be paid to maintaining the original wrist width to prevent progressive ulnar deviation of the wrist. OBF reconstruction was generally used alone.…”
Section: Graph Review and Results Recordingmentioning
confidence: 99%
“…Simple OBF reconstruction can generally cause wrist longitudinal instability, DRUJ instability and chronic pain [10]. Ota et al [21] also consider that the wrist width loss after Sauvé-Kapandji procedure is associated with the aggravated carpal ulnar deviation, therefore, attention should be paid to maintaining the original wrist width to prevent progressive ulnar deviation of the wrist. OBF reconstruction was generally used alone.…”
Section: Graph Review and Results Recordingmentioning
confidence: 99%
“…All patients achieved osseous union, wrist pain resolved or decreased, and means total range of forearm rotation increased by 23°. Ota N et al [ 19 ] concluded modified Sauve-Kapandji procedure was a useful reconstruction procedure in patients with severe RA with poor bone quality. 29 wrists of 23 patients were performed operation that involves rotating the resected ulnar segment 90 degrees and using it to bridge the gap between the sigmoid notch and the ulnar head.…”
Section: Discussionmentioning
confidence: 99%
“…Ota et al . 17 in 2013 reported satisfactory results with their own 1 modification of S-K procedure in which resected piece of ulna was used as a graft between ulnar head and ulnar notch of radius. The authors found that radioulnar width of the wrist, pseudarthrosis gap, and radioulnar distance were well maintained throughout the period.…”
Section: Discussionmentioning
confidence: 99%
“…Although satisfactory results are obtained in most cases, the instability of the proximal ulnar stump in both coronal, as well as sagittal planes remains the major complication causing pain and discomfort while doing daily activities, especially in pronation. 13 14 15 16 17 …”
Section: Introductionmentioning
confidence: 99%